PENGARUH PRODUKSI, HARGA INTERNASIONAL, DAN PDB PER KAPITA TERHADAP IMPOR BAWANG PUTIH DI INDONESIA - Mashuri; Ichsan; Ratna; Usman, Umaruddin (Jurnal Ekonomi Pertanian Unimal, 2025)
This study aims to determine the influence of production, international prices, and GDP per capita on garlic imports in Indonesia, The data used is time series data in the range of 1981-2022 obtained from World Bank and the Food and Agriculture Organization (FAO). This study uses a multiple linear regression analysis model with the E-views 10 application. The results of the study show that garlic production has a positive and insignificant effect on garlic imports in Indonesia. The international price of garlic has a negative and significant effect on garlic imports in Indonesia. Meanwhile, GDP per capita has a positive and significant effect on garlic imports in Indonesia. From the results of the research, it is suggested that the Indonesian government establish closercooperation and trade relations with the main garlic-producing countries, as well as increase the GDP per capita of the community.